Elasto-plastic stress analysis of thermoplastic matrix composite laminated and perforated plates under in-plane loading - Arlsan, N; Pihtili, H; Gur, M (Sage Publications Ltd, 2001)
The study presents an elasto-plastic stress analysis in symmetric and antisymmetric cross-ply reinforced thermoplastic matrix composite laminated plates. The thermoplastic matrix composite layer reinforced by long stainless steel fiber is manufactured by using moulds under the action of 2 MPa pressure and heating up to 200degreesC. A laminated and perforated plate consists of four thermoplastic matrix layers is reinforced cross-ply and bonded symmetrically or antisymmetrically. The first-order shear deformation theory and nine node Lagrangian finite element are used. The residual stresses and the expansions of plastic regions are illustrated for various cases. The in-plane load and the layer orientation angle are increased gradually.
Keywords: Finite-Element Analysis; Shells; Holes